Frequency Of Burnout Among Healthcare Professionals In A Tertiary Care Hospital, After The COVID-19 Pandemic - Abbasi, Yasira; Meraj, Lubna; Batool, Asma; Mansoor, Samreena; Muntaha, Sidra tul; Jalal, Anjum (Journal of Rawalpindi Medical College, 2023)
Objective: In this study, we plan to estimate the frequency of burnout among healthcare providers in a specialized teaching Hospital. Methods: A questionnaire based on the Copenhagen Burnout Inventory (CBI) including personal, work and client subscale was administered to various healthcare workers including staff nurses, residents and consultants. Results: When the demographic data of 100 participants was analyzed it showed that there were 39 (39 %) males and 61(61 %) females. The mean age of participants was 32.2 years. Professional categories enrolled were 40 nurses, 32 consultants and 28 postgraduate trainees. The mean level of personal burnout was 47.15±15.73, 38.53 ± 17.64 and 41.06 ± 15.78 among nurses, postgraduate trainees and consultants respectively. The level of work-related burnout was 45.95 ± 19.01, 36.60 ± 14.93 and 36.75 ± 14.99 among nurses, postgraduate trainees and consultants respectively. Whereas client-related burnout was found to be 42.62 ± 16.63, 27.67 ± 12.22 and 30.71 ± 18.04 among nurses, postgraduate trainees and consultants respectively. Burnout severity was higher among nurses, and also more commonly seen among females as compared to males. Lastly, younger respondents were more burned out compared to older respondents. Conclusion: In conclusion, addressing burnout among healthcare professionals, particularly nurses, is crucial for the well-being of the healthcare force and the safety and quality of patient care. The study’s recommendation for personal and institutional interventions is an essential step in mitigating this issue and ensuring a healthier, more effective healthcare system. Keywords: Burnout severity, moderate burnout, Copenhagen Burnout Inventory.